Radical simplicity : transforming computers into me-centric appliances - Hayes-Roth, Frederick (Hewlett-Packard Press strategic books, 2002)
Radical Simplicity: Transforming Computers Into Me-Centric Appliances The next computer revolution will be built around one person: you Imagine computers you can delegate to... computers that tell you things you want to know about ... adapt to your needs and preferences without being told ... work together on your behalf ... and respond to your voice, language, and gestures. It's all coming, sooner than you think -- and when it does, today's computers will be recognized as the dinosaurs they are. Radical Simplicity previews the "Me-Centric" computing revolution, in which the vast power of computers, communications, and software finally comes together to do your bidding-seamlessly, easily, and naturally. This "plain English" guide covers both the technology and its implications-and shows how you can prepare, starting today. How tomorrow's personalized intelligent appliances will extend your power, save you time, improve your productivity-and make life more fun From agents to Web services: emerging technologies that are making Me-Centric computing real New business opportunities in virtually every key industry-with realistic business cases The coming revolution in end-user expectations-and how IT must respond Rearchitecting products and services around users, not infrastructure Whether you're an executive or an IT professional, Radical Simplicity will help you take the lead in a new technology revolution that will dwarf everything that's come before it. About the Web Site You'll find even more articles, updates, and ideas about Me-centric computing at this book's Web site. www.radicalsimplicity.com.